Follicle cell trypsin‐like protease HrOvochymase: Its cDNA cloning, localization, and involvement in the late stage of oogenesis in the ascidian Halocynthia roretzi. Issue 4 (4th March 2016) - Mino, Masako; Sawada, Hitoshi
SUMMARY: We previously reported that the sperm trypsin‐like protease HrAcrosin and its precursor HrProacrosin participate in fertilization of the ascidian Halocynthia roretzi . The HrProacrosin gene is annotated in the H. roretzi genome database as Harore.CG.MTP2014.S89.g15383 ; our previously reported sequence of HrProacrosin gene appeared to include four nucleotides inserted near the 3′‐end of HrProacrosin, resulting in a frame‐shift mutation and a premature termination codon. The gene architecture of HrProacrosin and Harore.CG.MTP2014.S89.g15383 resembles that of Xenopus laevis ovochymase‐1 / OVCH1 and ovochymase‐2 / OVCH2, which encode egg extracellular polyproteases. Considering these new observations, we evaluated the cDNA cloning, expression, localization, and function of Harore.CG.MTP2014.S89.g15383, herein designated as HrOvochymase/HrOVCH . We found that HrOVCH cDNA consists of a single open reading frame of 1, 575 amino acids, containing a signal peptide, three trypsin‐like protease domains, and six CUB domains. HrOVCH was transcribed by the testis and ovary, but the majority of protein exists in ovarian follicle cells surrounding eggs. An anti‐HrOVCH antibody inhibited elevation of the vitelline coat at a late stage of oogenesis, during the period when self‐sterility is acquired. As trypsin inhibitors are reported to block the acquisition of self‐sterility during oogenesis, whereas trypsin induces the acquisition of self‐sterility and elevation of the vitelline coat in defolliculated ovarian eggs, we propose that HrOVCH may play a role in the acquisition of self‐sterility by late‐stage H. roretzi oocytes. Mol. Reprod. Dev. 83: 347–358, 2016. © 2016 Wiley Periodicals, Inc .